EXPLORING THE MODERATION ROLE OF TENDERPRENEURSHIP ON PROCUREMENT PLANNING AND VALUE FOR MONEY IN TANZANIA’S PUBLIC PROCUREMENT - RUTABA, Yohana Arsen (Journal of process management and new technologies, 2024)
This study investigates the moderating role of tenderpreneurship on the relationship between procurement planning and value for money within Tanzanian public procurement. Employing a cross-sectional research design, data were collected from procurement practitioners in Dodoma using structured questionnaires, with quantitative analysis conducted via SPSS and Hayes’ moderation approach. The research explores the direct effects of procurement planning and tenderpreneurship on value for money, as well as the moderation effect of tenderpreneurship on this relationship. Findings reveal that while procurement planning positively impacts value for money, tenderpreneurship negatively moderates this relationship, suggesting it can undermine procurement effectiveness. The study’s limitations include its cross-sectional design and regional focus, with recommendations for future research to employ longitudinal and qualitative methods. Practical implications highlight the need for transparency, capacity building, and technology adoption to enhance procurement practices. The research also calls for reforms to boost accountability and ensure value for money, offering original insights into the dynamics between tenderpreneurship, procurement planning, and value for money in public procurement.